2014
DOI: 10.1111/jcpp.12212
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of preparation and response control in ADHD: the role of DRD4 and DAT1

Abstract: This study detected specific effects of DRD4 7R on performance and brain activity related to attentional orienting and response preparation, while DAT1 10-6 was associated with elevated brain activity related to inhibitory response control, which potentially compensates increased impulsivity. As these genotype effects were additive to the impact of ADHD, the current results indicate that DRD4 and DAT1 polymorphisms are functionally relevant risk factors for ADHD and presumably other disorders sharing these end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 55 publications
(75 reference statements)
3
29
0
Order By: Relevance
“…A recent study from our lab with a cued CPT was consistent with Gizer and Waldman's findings regarding performance (children with DRD4 7R showed slower and more heterogeneous reaction times), as well as preparation problems as indicated by lower Cue-P3 and -CNV amplitude [111]. Importantly, these DRD4 effects were similarly present in children with ADHD and controls, and explained approximately a 4-5 % variance.…”
Section: Geneticssupporting
confidence: 86%
See 1 more Smart Citation
“…A recent study from our lab with a cued CPT was consistent with Gizer and Waldman's findings regarding performance (children with DRD4 7R showed slower and more heterogeneous reaction times), as well as preparation problems as indicated by lower Cue-P3 and -CNV amplitude [111]. Importantly, these DRD4 effects were similarly present in children with ADHD and controls, and explained approximately a 4-5 % variance.…”
Section: Geneticssupporting
confidence: 86%
“…Findings from our study may complement these results, as children with the DAT1 10-6 haplotype did not show higher commission error rates; rather (potentially as a compensatory mechanism) the No-Go-P3 amplitude as an electrophysiological marker of response inhibition was higher [111]. This demonstrates that accessory analysis of brain activity may uncover potentially compensatory neural processes that may lead to normal overt performance.…”
Section: Geneticssupporting
confidence: 77%
“…Reduced ERP components related to attentional orienting (Cue-P3), response preparation (contingent negative variation, CNV) and cognitive control during response inhibition (Nogo-P3) have repeatedly been reported. The Cue-P3 is linked to the posterior attention network mainly modulated by noradrenaline though processes triggering the Cue-P3 could also be under dopaminergic influence 11 . The subsequent Cue-CNV is a slow cortical potential with central topography reflecting resources allocated for response preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent Cue-CNV is a slow cortical potential with central topography reflecting resources allocated for response preparation. It is probably generated in the dorsal anterior cingulate, frontal cortex and midbrain dopaminergic nuclei, susceptible to dopaminergic modulation, and a lower CNV amplitude may reflect a persisting deficit in ADHD 1113 . The Nogo-P3 with sources in the prefrontal cortex and the anterior cingulate cortex (ACC) may reflect inhibitory response control modulated by dopaminergic activity.…”
Section: Introductionmentioning
confidence: 99%
“…5 The most frequently investigated candidate genes for ADHD, the dopamine D4 receptor gene (DRD4) and the dopamine transporter gene (DAT1, or SLC6A3), have also been associated with response inhibition performance and related brain activity. 7,8 DRD4 contains a variable number tandem repeat (VNTR) polymorphism in exon 3, for which the 7-repeat (7R) variant is considered a risk factor for ADHD. In vitro studies have indicated that the protein product of this gene, mainly expressed in the frontal cortex, may be less sensitive to dopamine if the 7R allele is present.…”
Section: Introductionmentioning
confidence: 99%